Kazakhstan Agricultural Sector Risk Assessment - Broka, Sandra; Giertz, Åsa; Christensen, Garry; Rasmussen, Debra; Morgounov, Alexei; Fileccia, Turi; Rubaiza, Rhoda (World Bank, Washington, DC, 2016)
Agriculture is among the most risk-prone sectors in the economies of Central Asia. Production shocks from weather, pests and diseases and adverse movements in agricultural product and input prices not only impact farmers and agri-business firms, but can also strain government finances. Some of these risks are small and localized and can be managed by producers. Others are the result of more severe, exogenous shocks outside agriculture that require a broader response. Failure to respond adequately to these more severe risks leads to a perpetual cycle of ‘shock-recovery-shock’ which reinforces poverty traps and compromises long-term growth. A broad-based program to improve livestock productivity is recommended to strengthen the resilience of livestock production systems and rangeland use in Kazakhstan. Proposed interventions include measures to: (i) reverse degradation of water, soil and vegetation cover; (ii) safeguard the long-term viability of rangeland ecosystems, while ensuring sustainable access to grazing land; and (iii) strengthen livestock services (veterinary, animal health, feed and fodder supply, destocking, water and grazing access, and weather and market information). These measures will enable farmers to manage their resources better, to respond to climate and market signals and to protect their resource base in times of drought. The recommendations developed under these three solution areas continue the underlying emphasis on mitigation as the foundation for risk management. They also highlight the mutually reinforcing benefits of measures to improve crop and livestock productivity for both risk management and sector growth.